Reproduction of Brevoortia aurea (Spix & Agassiz, 1829) (Actinopterygii: Clupeidae) in the Mar Chiquita Coastal Lagoon, Buenos Aires, Argentina - Lajud,Nicolás Agustín (2016)
ABSTRACT Reproductive biology of the Brazilian menhaden, Brevoortia aurea (Clupeiformes), was studied in Mar Chiquita Coastal Lagoon. Its abundance was analysed in relation to environmental variables, and the main biological-reproductive parameters were estimated: size at first maturity, batch and relative fecundity, frequency distribution of oocyte diameters and gonadosomatic index (GSI). Moreover, its reproductive cycle was analysed histologically. Samples were collected from May 2012 to April 2013. Once the spawning period was detected, extra samples were added (October and November 2013). The specimens were caught with gillnets, at a distance of 2,300 meters from the mouth of the lagoon. The highest abundances were observed in the months of October and November. Both macroscopic and microscopic analysis allowed to confirm that in these months the saraca spawn in the mixo-eurihaline area of the lagoon. Females were recorded in the five phases of ovarian development. Histological and frequency distribution of oocyte diameters characterized this species as a batch spawner with undetermined fecundity. The fecundity varied between 19,900 and 178,508 oocytes/female. Relative fecundity ranged between 41 and 381 oocytes/g female ovary free. The size at first maturity was estimated on 277 and 265 mm total length for females and males, respectively.